Logarithmic Derivative and the Angular Density of Zeros for a Zero-Order Entire Function - Zabolotskii, N. V.; Mostova, M. R. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
For an entire function of zero order, we establish the relationship between the angular density of zeros, the asymptotics of logarithmic derivative, and the regular growth of its Fourier coefficients.